Strategi Mengajar Bahasa Inggris pada Kelas Daring Selama Masa Pandemik Covid-19 di SMP Swasta F. Tandean Tebing Tinggi - Kaban, Susiana; Dalimunte, Ahmad Amin (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
It is a challenge for English teachers to be able to effectively transfer lessons that are usually taught directly in class but now have to be taught online due to the Covid-19 pandemic. The challenge of explaining English with a disconnect between teaching methods and how the content should be taught is part of a teaching strategy that should be prepared properly so that learning objectives can be achieved. This study is qualitative research aims to find out English teaching strategy performed by English teachers in online learning during pandemic Covid-19 at SMP Swasta F. Tandean Tebing Tinggi and their challenges during online teaching. Two English teachers contributed as the subject of the study. Obtained the data using observation, documentation, interview. Meanwhile, the data was analyzed through the following steps; koding data, reducing data, presenting data and drawing conclusions. It was found that the teachers used vary teaching strategies depending on the language skills to be achieved, they use videos uploaded to YouTube in conveying the material and utilize the WhatsApp group, and Zoom as a communication medium and google classroom as a place to collect assignments. Lack of student motivation and the internet connection were the challenges that teachers often complained.